Study guide and workbook to accompany economics of development - Bolnick, Bruce R. (New York ; London : Norton, 1996)
Theory and patterns. Guiding principles. Human resources. Capital resources production and trade.
Keywords: Economics; Economic policy; Economic development; Developing countries -- Economic policy